Den hedenske fyrstedigtnings samfundssyn - Malmros, Rikke (Historisk Tidsskrift, 2013)
The Pagan Skaldic Poets' View of Society(1-2) This study draws on the testimony of pagan skaldic court poetry to shed light on the nature of pre-Christian Viking Age society. Danish historians, dominated by the views of the national-liberal author C.F. Allen, have asked the following questions: "How can a society of magnates who are wealthy private landowners be subjugated to an initially weak Christian royal power? How can a Christian state be formed out of pagan chaos?" Of all Old Norse literary genres, tenth-century skaldic court poetry is the most reliable expression of the late pagan mentalité. Since it is a particularly difficult genre to cope with, the present author, an historian, has examined all available interpretations and has had her work scrutinized by an experienced philologist, Dr. Kristina Attwood. The very strict rules of skaldic verse, and in particular of dróttkvætt, placed great constraints on the poets and forced them to use a very narrow range of conventional topics. These ever-recurring conventional themes form the backbone of the present study. Fifteen poems, totalling 120-130 stanzas and dating mainly from the tenth century, form the corpus of pagan court poetry considered here. However, the well-known poems Ynglingatal and Háleygjatal are considered spurious and are therefore omitted, though they do not contradict the conclusions reached. Skaldic court poetry served to affirm the ethos of society as perceived by its rulers and their retinues. The skalds were paid to glorify the ruler. This study aims to define those qualities for which the ruler received praise. (3) The ruler and his retinue, feasting in the hall, formed the 'public audience' of the skaldic court poets. But the themes of their verse encompassed the entire society whose basis was the people. The people or peoples under the ruler's sway were named collectives, the names often being centuries old. Most words for 'people' mean an 'army' or a 'kindred', while their members are called the 'men' or the 'warriors'. (4) The countries often have names derived from those of their people. Human society was conceived of as an army that owns a land. (5) The ruler was always born of a prominent family descending from the enigmatic figure, Yngvi. The powerful jarls of Hladir claimed descent from the gods who were worshipped by the society. (6) The ruler was highly praised in his role as commander of the army, that is, the people. He was most often described as the one who leads the army in battle. Should he survive he must by definition have been victorious. (7) The ruler was seen as the all-powerful friend and leader of the people. He was the protector and defender of his territory. He belonged to the country as it belonged to him. The ruler could give a country 'in marriage' to a lesser magnate, a jarl or 'landruler', just as the powerful jarl of Hladir, by military and diplomatic means, won western Norway as his 'bride'. Countries and territories were hotly-contested targets of warfare. (8) In the second half of the tenth century, society in western Norway could be described as a pyramid of chieftaincies, with King Harald Blacktooth, according to his runic inscription, placing himself at the summit. Under him stood the powerful jarl of Hladir - and under him again his skalds placed sixteen lesser jarls. But the only magnates mentioned in skaldic poetry are those who have a leading public role as official chieftains or holders of public office. The jarl of Hladir commanded the naval levy called leiðangr. (9) The kings of early tenth-century Norway were protected by the gods and patronized their cults. In the last days of heathendom, the jarls of Hladir, who claimed descent from the gods, exhorted their poets to emphasize the public values of paganism and the cults of pagan deities. Religion pervaded the entire society. Rulership and military leadership in particular were reinforced by religion. (10) The ideology of skaldic poetry contradicts in every particular the national-liberal ideas of C.F. Allen. Vestiges of national-liberal ideas among Danish historians have caused them to address the problems of early Christian rulership in the wrong way. There was no organisational anarchy to be quelled; on the contrary, there existed a viable and functioning system of public rulership and delegated office to be built on. Pagan court poetry celebrates the internal cohesion of a society where the ruler is viewed as the central figure protecting his country, leading his people, levying and commanding the army, and connecting it all with the divine. At the root of the national-liberal historians' view of ancient Northern society is the concept of man in the 'state of nature' as conceived by John Locke: by the work of his hands and the tilling of the land man creates freedom and private property, whereas public power, particularly autocratic power, is against nature. Modern anthropologists have observed however that primitive peoples do not in fact live in a 'state of nature'. Private alienable property, consisting of 'strategic resources that sustain life', is unknown prior to the point when the 'state' emerges out of a background of 'chieftaincy'. To anthropologists such as Polanyi, Service, Claessen, and Skalník, 'chieftaincies' and 'states' are 'redistributive' societies where members of society give obligatory gifts of resources to a centre where a centrally placed person, the chieftain or head of state, distributes them for the benefit of all, and in the process gains power, prestige, and religious legitimacy. Skaldic court poetry commemorates a society that differs markedly from that envisaged by traditional Danish historiographers, but is in complete accordance with the experience of modern anthropologists. Pagan Nordic society, governed by chieftaincy, differed from the Christian state in degree, but not in kind.Translated by Helen Susan MacLean